Sensing Characteristics and Transduction Mechanism of WO3-based Si FET-type Humidity Sensor Using Pulse Measurement - Hong, Yoonki; Yun, Jonghyun; Han, Dongjin; Lee, Sung-Tae; Woo, Sung-Yun (Journal of semiconductor technology and science, 2025)
As accurate humidity monitoring and control are critical in both home and factory environments, the recent interest in Internet of Things-based smart humidity sensors has rapidly increased. However, conventional humidity sensors have disadvantages of large size, output signal drift, and hysteresis. Thus, this study investigates the sensing characteristics of a Si field-effect transistor-type humidity sensor using a pulse measurement method. A tungsten trioxide (WO3) thin film, which is adopted as a sensing material to detect the relative humidity (RH) of the ambient air in the test chamber, is deposited via radio frequency magnetron sputtering. Water vapor is stably generated using a well-equipped humidity generation system, and N2 gas, which is used as a medium for carrying the water vapor, is controlled via mass flow controllers to adjust the RH. Subsequently, highly reliable humiditysensing characteristics of the sensor are obtained at room temperature in the forms of transfer (ID-VCG) curves and transient drain currents (IDs), without any significant ID drifts owing to pulse measurement. The chemical reaction between water molecules and the WO3 sensing layer is explained, and the effect of the chemical reaction in terms of electrical changes in the sensor is analyzed using energy band diagrams. The results indicate that |ID| decreases by 46% as RH increases from 3.4% to 80.3%. Furthermore, the response and recovery times are 97 s and 190 s, respectively. KCI Citation Count: 0